Entrepreneurial Success in RM Based on the Development of Business Negotiations - Culipei, Laura- Catalina; Gîdilica, Constantin (The Journal of Accounting and Management, 2022)
Anyone can become enterprising if they have the desire to grow, the curiosity to face challenges and overcome obstacles. This motto was argued by the foreign development partners of the Republic of Moldova in the context of the development of a sustainable national economy. Namely the entrepreneurial activity becomes the foundation of the national strategies and by domains, and the sources of external financing are oriented towards this segment, which becomes a strategic one in the current period. In this context, the authors come up with an argument for the development of skills and competences of people involved in entrepreneurship. Or the main argument being the similarity of the skills of a successful entrepreneur and negotiator. Therefore, not only the association of the two forces is the object of the study, but also the need to develop more skills of those interested in the development of a successful entrepreneurship in the Republic of Moldova is a second argument.